(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
In 1677 the bell was sent abroad to be mended. The ornamentation, which consists of grapes and vine leaves, is of a kind not uncommon on bells made in the Netherlands in the seventeenth century. When the bell was sent to be recast the original French inscription of 1595 was reproduced (badly) and a second inscription in Dutch was added.